PRAWO JURYSPRUDENCYJNE JAKO PRAWNICZY DYSKURS ARGUMENTACYJNY (ZARYS PROBLEMATYKI) - Święcicka, Paulina (Zeszyty Prawnicze, 2016)
Jurists Law as Argumentative Discourse Summary A preeminent role of jurists in creation of Roman law has been many times underlined and sketched in the modern Romanist’s literature. Most of activities in which jurists engaged fall within the scope of what is named “the Jurists law” –“Juristenrecht”, i.e. the law that has been developed through the activity of the legal experts – the Roman jurists. Therefore the nature of this type of law can perhaps be determined on the best way by description of the main activity of these experts – for Roman Antiquity it means the group of secular representatives of Roman jurisprudence of the pre-classical and classical periodes, considered the era largo sensu in which the Roman law reached its highest development. This activity, aside from cavere and agere, consisted in respondere, i.e. to answer to questions concerning legal problems, and, in that way of explaining the law or – in other words – by means of interpretation – to create new rules, forming in time a great legal corpus. In this sense the interpretatio was to be considered the equivalent of the ius civile (Pomp. lib. sing. enchir. D. 1,2,2,12; Cic., De off. 3,16,65), as well as it was to be contrasted with enacted law. Nevertheless, it is in fact out of the question that such interpretation may denote the entire influence of the Roman jurists upon the development of the law. Several factors of the fundamental significance for existence and development of the Jurists law in Roman Antiquity can be indicated, such as: the continued existence of a group of individuals dedicated to law, and its application; the “personalized” education in law, as well as the scientific literature and techniques of reasoning received by the representatives of the Roman jurisprudence; and finally – the freedom of discussion and disputation that has been absolutely in favor of the divergence of opinions and contradictions of solutions of legal problems that lead to the phenomena of the ius controversum. On the other hand, a particular uncertainty and unpredictability of the Jurists law has to be mentioned as an unavoidable outcome of such broadly understood freedom of contradictory opinions and discursive way of its formation. It was a peculiar aspect of the Jurists law and for this evaluation of no importance is that Ancient Romans appreciated such uncertainty, or – being familiar with controversies – regarded it as a normal feature of the law, because for them it was a jurist – not a “legislator” who worked out a rule of law and determined its application. All these give the basis to propose the thesis about the possibility of speaking about the Jurists Law as an argumentative discourse provided by professionals and operated in connection with some principles and rules that may or should be determine